2014
DOI: 10.1534/g3.113.009738
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes and Proteomes Define Gene Expression Progression in Pre-meiotic Maize Anthers

Abstract: Plants lack a germ line; consequently, during reproduction adult somatic cells within flowers must switch from mitotic proliferation to meiosis. In maize (Zea mays L.) anthers, hypoxic conditions in the developing tassel trigger pre-meiotic competence in the column of pluripotent progenitor cells in the center of anther lobes, and within 24 hr these newly specified germinal cells have patterned their surrounding neighbors to differentiate as the first somatic niche cells. Transcriptomes were analyzed by microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 60 publications
5
46
0
Order By: Relevance
“…S6) (30). Some AGO members are specifically expressed in flowers (29,30) and are further enriched in either somatic or germinal cells of anthers (19,31,32). Presumably, this AGO expansion reflects a functional diversification of plant small RNAs for roles specific to anther developmental stages and cell types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S6) (30). Some AGO members are specifically expressed in flowers (29,30) and are further enriched in either somatic or germinal cells of anthers (19,31,32). Presumably, this AGO expansion reflects a functional diversification of plant small RNAs for roles specific to anther developmental stages and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The binding partner of meiotic phasiRNAs has not yet been reported. Based on transcriptional analysis of lasermicrodissected cell types (19,32), plus the RNA-seq and microarray profiling of different anther stages (Dataset S6), we found that the expression profile of maize AGO18b matches the expression timing of meiotic phasiRNAs. Both AGO18b transcripts and proteins are enriched in the tapetal and meiotic cells (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They posit that these fundamental differences in meiotic processes evolved to accommodate hemizygosity of the X chromosome. Zhang et al (2014) examined the transcriptomes and proteomes during the differentiation of maize anthers, a model system well suited for this study because of the relative ease of collecting tissues at different developmental stages. In angiosperms, the germline arises from somatic flower cells through a switch from mitotic proliferation to meiosis.…”
Section: Different Molecular Mechanisms Operate In Male and Female Gamentioning
confidence: 99%
“…Two other articles examine differences in the evolution of sex chromosomes: Blackmon and Demuth (2014) look at the evolutionary turnover of sex chromosomes in beetles and Kirkpatrick and Guerrero (2014) use the recombining region of sex chromosomes to measure the strength of sexually antagonistic selection. Finally, two studies focus on gametogenesis-sex differences in meiosis in Caenorhabditis elegans (Checchi et al 2014) and the specification and development of germinal cells in maize (Zhang et al 2014).…”
mentioning
confidence: 99%